2019
DOI: 10.1111/cid.12791
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and severity of peri‐implantitis bone defects

Abstract: Background: Peri-implant defect morphology has shown to potentially impact upon the reconstructive outcomes for the management of peri-implantitis. Given the role that defect morphology plays upon the decision-making in the treatment of peri-implantitis, the present study aimed at assessing the morphology and severity of peri-implantitis bone defects and to insight on the patient-, implant-and site-related variables associated to these. Material and Methods:A cone-beam computed tomography study was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
159
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 40 publications
4
159
0
12
Order By: Relevance
“…The original concepts as outlined by previous authors hold true for implants. Monje et al () reported that 77.2% of the peri‐implantitis cases had inadequate access for cleansability. Serino and Ström () found that 74% of the implants had no access to proper plaque control and highlighted the role of prosthesis design.…”
Section: Introductionmentioning
confidence: 99%
“…The original concepts as outlined by previous authors hold true for implants. Monje et al () reported that 77.2% of the peri‐implantitis cases had inadequate access for cleansability. Serino and Ström () found that 74% of the implants had no access to proper plaque control and highlighted the role of prosthesis design.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Comparably, peri-implantitis is a pathologic condition associated with biofilm formation and is characterized by "inflammation in the peri-implant mucosa and a progressive loss of supportive bone." [4][5][6][7][8] Strong evidence suggests that periodontitis is a risk factor for peri-implant disease. 5,9 Periodontitis and peri-implantitis have similar clinical and radiographic features but evident molecular and histopathological differences.…”
Section: Introductionmentioning
confidence: 99%
“…Peri-implantitis was defined as the combination of bleeding on gentle probing (BOP) with or without suppuration, probing depths (PD) ≥ 6 mm, and radiographic marginal bone loss (MBL) (i.e., interproximal bone levels ≥ 3 mm apical of the most coronal portion of the intraosseous part of the implant) [2]. All implant sites were associated with an advanced bone loss (> 6 mm/> 50% of the implant length) [14] and were clinically stable (i.e., no manually detected mobility) but were scheduled for explantation due to the advanced disease progression. The study protocol no.…”
Section: Subjects and Implant Datamentioning
confidence: 99%
“…Peri-implantitis lesions extend apical and are commonly associated with a circumferential pattern of bone loss [1,10]. Intraoperative clinical and radiographic assessments, however, do not fully represent the extension of peri-implantitis defects [11][12][13][14]. Moreover, the morphology of the remaining bone being exposed to masticatory forces has not been described so far.…”
Section: Introductionmentioning
confidence: 99%